Editorial: scoring systems in primary biliary cholangitis – time to make a move. Issue 8 (21st March 2017) - Mells, G. F.; Jones, D. E.
Abstract : Linked Content This article is linked to Yang et al papers. To view these articles visithttps://doi.org/10.1111/apt.14010 andhttps://doi.org/10.1111/apt.13927 .